Pengembangan E-Modul Praktikum Fisika Berbasis Inkuiri pada Materi Elastisitas dan Hukum Hooke untuk Siswa SMA/SMK - Arini Rosa Sinensis; Thoha Firdaus; Aninatus Sofiah; Widayanti Widayanti (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
Utilization of Technology and Information must be optimized properly in learning, one of which is used to develop teaching materials. The aim of the research is to develop an inquiry-based physics-based E-module on elasticity and Hooke's law. The method used is Research and Development (R&D). The development procedure uses a 4D model consisting of Define, Design, Develop and Disseminate. The instrument used is a validation sheet and product practicality in the form of a questionnaire. The location for testing this E-module product is at SMK Nurul Huda Sukaraja with a sample of 20 students from class XI Multimedia. The results of the feasibility test from experts (media and materials) are very valid with a percentage gain of 83.7%. The results of the small-scale e-module practicality test results obtained a percentage of 95.69%, the large-scale e-module practicality test results obtained a percentage of 95.38% with very practical criteria. Thus the physics practicum e-module developed is feasible and practical to be used as teaching material for high school/vocational high school physics practicum learning.